Denosumab Improves Glycaemic Parameters in Postmenopausal Osteoporosis Patients with Combined Type 2 Diabetes Mellitus: Effect of Denosumab on Type 2 Diabetes - Wang, Ke; Gao, Liu; Liu, Chang; Bao, Xiaoxue; Tian, Yawei; Li, Yukun (Cellular and Molecular Biology, 2023)
This study aimed to determine whether RANKL inhibitors in postmenopausal osteoporosis patients with combined type 2 diabetes mellitus (T2DM) could improve their glucose metabolism index. First of all, 84 patients affected with postmenopausal osteoporosis with combined T2DM attending the Department of Endocrinology at the Third Hospital of Hebei Medical University were selected and randomized into two groups of 42 patients each. One group was given Denosumab 60 mg once every six months (denosumab group, D.G.), and the other group was given 2 mg ibandronate once every three months (ibandronate group, I.G.). Blood glucose parameters were compared before and after treatment in both groups and serum active GLP-1 levels and DPP-4 levels were also assessed. After treatment, there was no significant difference in fasting glucose between the two groups, but there was a significant decrease in fasting glucose in the Denosumab Group (D.G.) compared to before treatment. There was a significant difference in 2-hour postprandial glucose (2hPG) between the two groups after treatment, with the D.G. being lower than the ibandronate group (I.G.). Glycosylated haemoglobin (HbA1c) was lower in the D.G. than in the I.G. after treatment, but the difference between them was insignificant. In the D.G., serum active GLP-1 levels increased after treatment, and serum DPP-4 levels decreased. Serum GLP-1 and DPP-4 levels in the I.G. did not change compared with those before treatment. In conclusion, In the clinical management of postmenopausal osteoporosis patients with combined T2DM, the choice of RANKL inhibitors as anti-osteoporosis therapy may benefit their glycaemic parameters by elevating serum active GLP-1 levels and decreasing serum DPP-4 levels.